Respostas
respondido por:
4
Oi Tiago
4^x - 5*2^x + 6 = 0
(2^x)² - 5*2^x + 6 = 0
y = 2^x
y² - 5y + 6 = 0
delta
d² = 25 - 24 = 1
d = 1
y1 = (5 + 1)/2 = 3
y2 = (5 - 1)/2 = 2
2^x = 3
xlog(2) = log(3)
x = log(3)/log(2)
2^x = 2
x = 1
4^x - 5*2^x + 6 = 0
(2^x)² - 5*2^x + 6 = 0
y = 2^x
y² - 5y + 6 = 0
delta
d² = 25 - 24 = 1
d = 1
y1 = (5 + 1)/2 = 3
y2 = (5 - 1)/2 = 2
2^x = 3
xlog(2) = log(3)
x = log(3)/log(2)
2^x = 2
x = 1
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás